Selumetinib for plexiform neurofibromas in neurofibromatosis type 1: a single-institution experience - Espirito Santo, Vera (2021)
Background Plexiform neurofibromas (PN) are the most frequent tumors associated with Neurofibromatosis type 1 (NF-1). PN can cause significant complications, including pain, functional impairment, and disfigurement. There is no efficient medical treatment and, surgical resection of large PN is frequently infeasible. Selumetinib (AZD6244/ARRY-142886) is a mitogen-activated protein kinase enzyme (MEK1/2) inhibitor and works by targeting the MAPK pathway. It is an investigational treatment option for inoperable symptomatic PN associated with NF-1. Herein, we describe a single institutional experience with selumetinib for inoperable PN in NF-1. Methods Case series study of demographics, clinical, baseline characteristics, treatment effect, and follow-up of consecutive genetically confirmed NF1 patients with inoperable PN associated with significant or potential significant morbidity treated with selumetinib (April 2018 to April 2019). Results Nineteen patients were treated with selumetinib. Predominant target locations were head and neck (31.6%, 6/19), chest (26.3%, 5/19) and pelvis (21%, 4/19) and the most important comorbidities were disfigurement (47.4%, 9/19) and pain (26.3%, 5/19). The mean follow-up time was 223 days (range 35-420 days). All but one had sustained clinical improvement, mainly in the first 60-90 days of treatment. In one patient, the treatment was suspended after 168 days (lack of clear benefit and left ventricular ejection fraction drop). There were no adverse effects leading to treatment suspension. Conclusions In the first observational study of selumetinib for NF-1 associated PN we showed that the drug was associated with clinical and radiological improvement. Our study also confirms the safety described in the clinical trials.